MAN ON THE RADIO - Allanegui, John Patrick I. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
The essay is the author’s reflection on his late father whom he remembers best as a radio announcer. it centers on their family radio as an object of recollection as it portrays their complicated relationship, traversing between memory and insight, between sound and silence.